Clinical study of geriatric dermatoses - Devi, M. Vairaprabha; Manikandan, N. C. (International Journal of Research in Dermatology, 2019)
Background: Diagnosis of geriatric dermatoses is a challenging job for the Physician due to the involvement of many intrinsic and extrinsic ageing factors. The present study was done with the aim to determine the clinical profile and pattern of dermatological manifestations in elderly people aged 60 and above and to analyze the correlation of various geriatric dermatoses with systemic diseases. Methods: This was a prospective study done on 200 elderly individuals aged 60 years and above attending the outpatient clinic of Department of Dermatology, RGGGH and the outpatient clinic of Department of Geriatrics, RGGGH during the study period from October 2015 to September 2016. Detailed history of cutaneous complaints, present and past medical complaints were taken. A complete general, physical, systemic and dermatological examination was done in all patients and the findings were noted and analysed. Results: Male preponderance was observed (M:F-1.8:1). Maximum number of patients (n=166) belonged to the age group of 60-69 years. Wrinkling of the skin is the commonest physiological geriatric dermatoses. Among the pathological changes, infections and infestations were observed in 27.5% of the study population. Fungal infection was the commonest among them (20%) followed by bacterial (18%) and viral (12%). Diabetes Mellitus was the commonest associated systemic ailment and was observed in about 31.5% of the study population. Conclusions: Geriatric dermatoses occur in the elders due to extrinsic and intrinsic ageing factors. Crinkles were the commonest physiological geriatric dermatoses and benign tumours were the commonest pathological ones. Educating the elders about proper skin care along with the early diagnosis and treatment of their cutaneous ailments would help them to lead a productive and healthy life.